Development of Art and Architecture in Sultanate Period with Special Reference to Slave and Khali Dynasty - Mishra, Dr.Akhaya Kumar (International Journal of Scientific Research and Management (IJSRM), 2017)
According to the existing research and discourses, Art and Architecture have been considered two most crucial things that reflect upon a country and its people. In Indian context, understanding them holds special significance. The word “Indian” comes with a heavy baggage of traditions, culture and ethos, which is unique and adds divinity to almost every act of life. Both art and architecture are narratives of this unique Indian baggage. There are significant examples of art works in the history of architecture. India is the only country with the largest and most diverse mixture of tradition and culture. The fascinating nation is so enticing where the exotic monuments and enchanting destinations speak volumes about the tradition and culture of Indian people. India is home to many of the finest cultural symbols of the world which includes, mosques, mausoleum, forts, sculptures, architecture, etc.. In this regard some of the prestigious and spectacular World Heritage Sites in India during Sultanate period can be discussed. They are the Quwwat-ul-Islam mosque, the Qutb Minar, Adhai-din-ka-Jhompra, Sultan Ghari mosque, Alai Darwaza, Jama ‘at Khana mosque, Ukha masjid at Bayana etc.